2018
DOI: 10.2459/jcm.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Is the time between first diagnosis of paroxysmal atrial fibrillation and cryoballoon ablation a predictor of efficacy?

Abstract: In the total cohort, cryoablation was performed after a median of 36 months from the point of the patient diagnosis with drug refractory symptomatic recurrent atrial fibrillation. The early-treatment group was composed of 130 (25%) patients, whereas the late-treatment group had 380 (75%) patients. Both cohorts had similar baseline clinical characteristics. Of 510 patients, 22 had a complication related to the procedure with no difference between the two groups. Multivariable analysis showed that the risk of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…This systematic review and meta‐analysis concluded that a longer DTAT is associated with AF recurrence after ablation as early as 12 and 36 months have been demonstrated to have a profound effect on the AF recurrence. Interestingly, shorter DTAT is shown to have a higher AF freedom in both paroxysmal and persistent AF, as shown by studies by Hussein et al who included 100% persistent AF samples and Lunati et al which included a 100% paroxysmal AF samples . Paroxysmal AF occasionally (10%‐20%) progress to persistent AF and probably, considering the delay in that 10%‐20% patients, DTAT is still a significant predictor of AF recurrence .…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…This systematic review and meta‐analysis concluded that a longer DTAT is associated with AF recurrence after ablation as early as 12 and 36 months have been demonstrated to have a profound effect on the AF recurrence. Interestingly, shorter DTAT is shown to have a higher AF freedom in both paroxysmal and persistent AF, as shown by studies by Hussein et al who included 100% persistent AF samples and Lunati et al which included a 100% paroxysmal AF samples . Paroxysmal AF occasionally (10%‐20%) progress to persistent AF and probably, considering the delay in that 10%‐20% patients, DTAT is still a significant predictor of AF recurrence .…”
Section: Discussionmentioning
confidence: 86%
“…After assessing eight full‐text for eligibility, we excluded two because of (a) no outcome of DTAT on the recurrence of AF and (b) outcome cannot be used for meta‐analysis due to different reporting. We included six studies in the qualitative synthesis and six studies in meta‐analysis (Figure ; Table ) . Five studies were prospective cohorts, and one study was a retrospective cohort.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations